Using 3D laser scanning to analyze heritage structures: the case study of Egyptian Palace - Marzouk, Mohamed (Journal of Civil Engineering and Management, 2020)
Preservation of heritage buildings should be carried out to get a better understanding of the behavior of their structures and keep them in a good condition. As such, corrective diagnosis of heritage buildings health conditions would help to identify potential risks and take remedy actions. This paper presents a framework for heritage Building Information Modeling (HBIM) application in Egyptian Heritage buildings. The framework is capable of utilizing processed point clouds using 3D laser scanning to create different purpose BIM models at the different levels of development to simulate the structural performances under different types of actions. The paper illustrates an extensive structural analysis for Tosson palace in Cairo – Egypt to assess its health state to assure its sustainability for future use.